2020
DOI: 10.3390/app11010170
|View full text |Cite
|
Sign up to set email alerts
|

A Review on the Importance of Microbial Biopolymers Such as Xanthan Gum to Improve Soil Properties

Abstract: Chemical stabilization of soils is one of the most used techniques to improve the properties of weak soils in order to allow their use in geotechnical works. Although several binders can be used for this purpose, Portland cement is still the most used binder (alone or combined with others) to stabilize soils. However, the use of Portland cement is associated with many environmental problems, so microbiological-based approaches have been explored to replace conventional methods of soil stabilization as sustaina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 42 publications
1
24
0
Order By: Relevance
“…The XG initially lled in or near the pores either developed into bonding surface, merged into bridge links, or accumulated into ber matrices, which connected the adjacent soil frameworks closely 23,25,26,29,42 . As the contact area among the soil particles increased, the integrity of soil particles was enhanced, and the particle size of soil skeleton particles became larger.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The XG initially lled in or near the pores either developed into bonding surface, merged into bridge links, or accumulated into ber matrices, which connected the adjacent soil frameworks closely 23,25,26,29,42 . As the contact area among the soil particles increased, the integrity of soil particles was enhanced, and the particle size of soil skeleton particles became larger.…”
Section: Resultsmentioning
confidence: 99%
“…Existing studies have shown that biopolymers have excellent performance in soil reinforcement, promoting vegetation growth and desert control [21][22][23] . As one of the biopolymers, Xanthan gum (XG) can provide higher uncon ned compressive strength than guar gum and β-glucan 24 .…”
Section: Introductionmentioning
confidence: 99%
“…It can be expected that xanthan gum biopolymers can provide stronger hydrogen or electrostatic bonding by curing [35]. With increasing curing time, the crosslinking of the biopolymer gel with the negatively charged clay surface becomes stronger, leading to an increase in the bonding strength between particles [36,37]. Figure 5 shows that the UCS for both the biopolymer-stabilized and fiber-reinforced soil increases considerably when cured in the air.…”
Section: Effect Of Fibers and Biopolymer On Soil Strengthmentioning
confidence: 99%
“…The potential and recent applications of xanthan gum biopolymer, with a particular focus on improving soil properties is reviewed by Mendonça et al [4]. Xanthan gum is a polysaccharide formed by aerobic fermentation of sugar by Xanthomonas campestris.…”
Section: Industrial Microbiologymentioning
confidence: 99%